Pengaruh Kompetensi Guru dan Disiplin Kerja terhadap Motivasi Serta Implikasinya pada Kinerja Guru di Sekolah Dasar Pelita Fajar - Apriany Listarida; Dety Mulyanti; Kosasih Kosasih (Departement of Mathematics Education, 2023)
The results of the performance and competency survey of teachers at Pelita Fajar Elementary School in using media or learning resources are appropriate using LKS as a guide, but teachers should use additional guidelines such as teaching modules as a guide. The aim of this research is to analyze the influence of teacher competence, work discipline, motivation on teacher performance at Pelita Fajar Elementary School. The benefits of this research are providing additional information to develop theoretically based strategies regarding the Influence of Teacher Competency and Work Discipline on Motivation and the Implications for Teacher Performance at Pelita Fajar Elementary School. The object of this research is Pelita Fajar Elementary School. This research uses a survey research method with a quantitative approach. Based on the research results, it can be concluded that the compensation variable (X1) has a significant influence on the work discipline variable (X2). The work discipline variable (X2) is 0.610 (< 0.05), so it can be concluded that the work discipline variable (X2) has a significant influence on the motivation variable (Y). This shows that at SD Pelita Fajar teachers master the learning materials given to students. Teachers teach according to the field of science they are studying. Teachers master the subject matter they teach. Teachers master the theoretical concepts of the subjects they teach. Teachers develop learning materials according to the environment around students. Teachers develop learning materials using innovative learning. Teachers utilize technology in teaching in class.